Construction of an Escherichia coli chassis for efficient biosynthesis of human-like N-linked glycoproteins - Bao, Zixin; Gao, Yuting; Song, Yitong; Ding, Ning; Li, Wei; Wu, Qiong; Zhang, Xiaomei; Zheng, Yang; Li, Junming; Hu, Xuejun (Frontiers in Bioengineering and Biotechnology, 2024)
The production of N-linked glycoproteins in genetically engineered Escherichia coli holds significant potential for reducing costs, streamlining bioprocesses, and enhancing customization. However, the construction of a stable and low-cost microbial cell factory for the efficient production of humanized N-glycosylated recombinant proteins remains a formidable challenge. In this study, we developed a glyco-engineered Escherichia coli chassis to produce N-glycosylated proteins with the human-like glycan Gal-β-1,4-GlcNAc-β-1,3-Gal-β-1,3-GlcNAc-, containing the human glycoform Gal-β-1,4-GlcNAc-β-1,3-. Our initial efforts were to replace various loci in the genome of the E. coli XL1-Blue strain with oligosaccharyltransferase PglB and the glycosyltransferases LsgCDEF to construct the E. coli chassis. In addition, we systematically optimized the promoter regions in the genome to regulate transcription levels. Subsequently, utilizing a plasmid carrying the target protein, we have successfully obtained N-glycosylated proteins with 100% tetrasaccharide modification at a yield of approximately 320 mg/L. Furthermore, we constructed the metabolic pathway for sialylation using a plasmid containing a dual-expression cassette of the target protein and CMP-sialic acid synthesis in the tetrasaccharide chassis cell, resulting in a 40% efficiency of terminal α-2,3 sialylation and a production of 65 mg/L of homogeneously sialylated glycoproteins in flasks. Our findings pave the way for further exploration of producing different linkages (α-2,3/α-2,6/α-2,8) of sialylated human-like Nglycoproteins in the periplasm of the plug-and-play Escherichia coli chassis, laying a strong foundation for industrial-scale production.